PHYLOGENETIC RELATIONSHIPS OF INDONESIAN BANANA CULTIVARS INFFERED FROM TRNL-F INTERGENIC SPACER OF CHLOROPLAST DNA - Amin Retnoningsih; Rita Megia; Alex Hartana (Floribunda, 2014)
A phylogenetic relationship of Indonesian banana cultivars was conducted using trnL-F intergenic spacer of chloroplast DNA sequences. The ingroup was 39 banana accessions from various genomic groups in Indonesia consisting of 9 AA/AAA; 11 AAA; 2 BB; 13 AAB; and 4 ABB cultivars and 12 sequences of different taxa of Musa downloaded from GenBank consisting of 4 AA wild; 1 AA; 3 AAB; and 4 ABB cultivars. Two accessions from section Rhodoclamys and Australimusa were used as the outgroup. The 39 accessions of the ingroup and the 2 accessions of the outgroup were analyzed using primers of the trnL-F intergenic spacer. The results showed that sequence of the trnL-F region can clearly distinguish 40 banana accessions having the A-type chloroplast (AA wild; AA; AA/AAA; AAA; AAB; and ABB) from those 11 accessions having the B-type chloroplast (BB, AAB, and ABB). The A-type chloroplast accessions are most probably derived from female Musa acuminata, while the B-type chloroplast accessions may be derived from female M. balbisiana. However, the specific M. acuminata ancestor of each cultivar remains unidentified.